Reflexions a propos d'un Fonds monetaire international utilisant exclusivement le DTS. (Pamphlet Series, 1979)
This paper discusses the possibility of an IMF that would be based fully on the special drawing right (SDR). The paper explores the basic economic justification for a General Department restructured in this way, the broad outline of the structure that would have to be established, the liquidity effects that would have to be considered, and the effects of these changes on other provisions. It also discusses some of the simplifications that would be brought about, and the steps involved in the transition from an IMF consisting primarily of currencies to one based fully on the SDR.